Long-term surgical outcomes in patients with drug-resistant temporal lobe epilepsy and no histological abnormalities - J.C. Benedetti-Isaac; M. Torres-Zambrano; J. Fandiño-Franky; J. Dussán-Ordóñez; A. Herrera-Trujillo; R. Guerra-Olivares; G. Alcalá-Cerra (Neurología (English Edition), 2013)
Introduction: Reports on surgical outcomes in patients with drug-resistant temporal lobe epilepsy without histological abnormalities are scarce. Methods: Retrospective review of data from patients with drug-resistant temporal lobe epilepsy and no histopathological alterations who underwent anterior mesial temporal lobectomy. We analysed the following variables: age, sex, age at seizure onset, age at surgery, time elapsed between diagnosis and the date of the surgery, follow-up time, and classification according to the Engel rating scale. Results: From a database of 256 temporal lobectomies, 21 were identified as meeting the inclusion criteria. The average age upon diagnosis of epilepsy was 8.3 years and average age at time of surgery was 28.6 years. The mean time elapsed between diagnosis and surgery was 20.2 years. After a mean follow-up of 6.5 years, 90.5% of the patients showed favourable outcomes (classes i and ii) and 42.9% were seizure-free (class IA). Comparative analysis of the variables revealed that average age at seizure onset was the only statistically significant difference between groups, with age at onset being lower in patients with favourable outcomes. Conclusion: Although long-term surgical outcomes were favourable for a large majority of patients, the percentage of seizure-free patients is lower than in patients with lesional epilepsy and comparable to that previously reported in the literature. Resumen: Introducción: Los reportes de los resultados quirúrgicos en los pacientes con epilepsia fármaco-resistente del lóbulo temporal sin anormalidades histológicas son escasos. Métodos: Fueron revisados retrospectivamente los datos de los pacientes con epilepsia del lóbulo temporal tratados con lobectomía temporal anterior con amígdalo-hipocampectomía que no presentaban alteraciones en los estudios histopatológicos. Fueron analizadas las variables: edad, género, edad al inicio de las crisis epilépticas, edad al momento de la cirugía, tiempo de evolución de la epilepsia desde el diagnóstico hasta la fecha de la cirugía, periodo de seguimiento y clasificación según la escala de Engel. Resultados: De una base de datos de 256 lobectomías temporales, fueron identificados 21 pacientes que cumplieron los criterios de inclusión. El promedio de edad a la cual se realizó el diagnóstico de epilepsia fue 8,3 años, al momento de la cirugía fue 28,6 años y de tiempo transcurrido desde el diagnóstico hasta la cirugía fue 20,2 años. Tras un seguimiento promedio de 6,5 años, el 90,5% obtuvo resultados favorables (clases i y ii) y el 42,9% estaba libre de crisis (clase iA). Tras el análisis comparativo de las variables estudiadas, solo existieron diferencias estadísticamente significativas en la edad de inicio de las crisis, siendo inferior en los pacientes que obtuvieron resultados favorables. Conclusión: Aunque en la gran mayoría de los pacientes los resultados quirúrgicos a largo plazo fueron favorables, la proporción de pacientes libres de crisis es inferior a la de los pacientes con epilepsia lesional y comparables con lo reportado previamente en la literatura. Keywords: Epilepsy surgery, Drug-resistant epilepsy, Lobectomy, Temporal lobe epilepsy, Normal magnetic resonance imaging, Palabras clave: Cirugía de epilepsia, Epilepsia médicamente refractaria, Lobectomía, Epilepsia del lóbulo temporal, Resonancia magnética normal